Circular Economy Training of Halal Product Process in UMKM Mentored By PD Nasyiatul Aisyiah, Sidoarjo - Wahyuni, Hana Catur; Andriani Eko P; Hasan Ubaidillah; Bilqis Sabrina A; M. Amin Zakariyah (Kontribusia : Research Dissemination for Community Development, 2025)
This community service activity aims to increase the capacity and understanding of Micro, Small and Medium Enterprises (MSMEs) under the guidance of PD Nasyiatul Aisyiyah Sidoarjo regarding the circular economy concept in the production process of halal products. This training involves MSME entrepreneurs in implementing resource efficiency strategies, waste utilization and sustainable product innovation. The method includes training and mentoring which will be held in the period August-September 2024. The training will be held on September 8 2024 with the topics (1) application of circular economy in the process of halal products for MSMEs, (2) business management, (3) forms of processing waste from halal product processes and (4) circular economy practices through the use of waste as planting media. The results of the activity showed an increase in participants' knowledge and awareness of the importance of a circular economy and halal product processes. Apart from that, participants are also committed to implementing this concept in their business operations to increase product competitiveness and expand markets. It is hoped that this activity can contribute to sustainable economic development in the Sidoarjo region.